The demographic challenge in Castilla y León (Spain): an unbalanced region with an aged population (2022)
Castilla y León is a region with demographic features different from other Spanish areas. It is characterized by the loss of demographic numbers, the unequal distribution of its inhabitants, the emptying and masculinization of the rural environment and strong aging. All these issues that have been occurring since the mid-twentieth century are considered a priority in the national policy of the demographic challenge that requires new responses from the political action and change the look towards this territory.   The objective of this work consisted of analyzing all these characteristics present in the population of this region and which were key for land use planning and for the planning of social resources for the population. For this purpose, various population censuses and registers in Spain were used to analyze the variables mentioned above and to obtain the necessary data for the preparation of maps and graphs that facilitated the understanding of these phenomena through the use of cartographic applications and geographic information systems (GIS).    The situation of Castilla y León is complicated by its size since it is the largest region in Spain, and the scenario that emerges after the analysis reflects an increasingly depopulated and territorially unbalanced space: the population is mainly located in the cities, while the rural areas are emptying, with an increasingly aging population, masculinized and without replacement due to the fall in the birth rate. All of these factors have a negative impact on the provision of public services such as health and education, making it difficult to maintain infrastructures and making it more expensive to reach and improve communications. More importantly, the principle of territorial equity is lost and organizational and management problems are produced in the local administrations.